"FEATURES OF TEACHING READING AND WRITING TO INTELLECTUALLY DISABLED CHILDREN (Multidisciplinary Journal of Science and Technology, 2025)
This scientific article describes how children with mental disabilities are taught to write and read in the native language and literature classes of boarding schools.